2009
DOI: 10.3732/ajb.0800207
|View full text |Cite
|
Sign up to set email alerts
|

Malpighiales phylogenetics: Gaining ground on one of the most recalcitrant clades in the angiosperm tree of life

Abstract: The eudicot order Malpighiales contains ∼16000 species and is the most poorly resolved large rosid clade. To clarify phylogenetic relationships in the order, we used maximum likelihood, Bayesian, and parsimony analyses of DNA sequence data from 13 gene regions, totaling 15604 bp, and representing all three genomic compartments (i.e., plastid: atpB, matK, ndhF, and rbcL; mitochondrial: ccmB, cob, matR, nad1B-C, nad6, and rps3; and nuclear: 18S rDNA, PHYC, and newly developed low-copy EMB2765). Our sampling of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
277
2
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(328 citation statements)
references
References 165 publications
(288 reference statements)
30
277
2
19
Order By: Relevance
“…Results from our analyses (Fig. S1) were identical to recent studies but were better supported in key parts of the phylogeny (21,28). Here, Elatinaceae + Malpighiaceae is established as a well-supported (86 maximum-likelihood bootstrap percentage, 1.0 Bayesian posterior probability) sister clade to Centroplacaceae.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Results from our analyses (Fig. S1) were identical to recent studies but were better supported in key parts of the phylogeny (21,28). Here, Elatinaceae + Malpighiaceae is established as a well-supported (86 maximum-likelihood bootstrap percentage, 1.0 Bayesian posterior probability) sister clade to Centroplacaceae.…”
Section: Resultssupporting
confidence: 74%
“…To properly root and date our phylogeny, we first clarified the closest relatives of Malpighiaceae. Previous phylogenetic studies (26)(27)(28) have identified the radially flowered, species poor clades Centroplacaceae (∼5 species) and Elatinaceae (35 species) as successive sisters to the species rich Malpighiaceae (∼1,300 species) (species diversity counts are from refs. 29 and 30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Euphorbiaceae é uma das maiores e mais diversas famílias das angiospermas (Govaerts et al 2000, Radcliffe-Smith 2001, sendo a maior dentro da ordem Malpighiales (Wurdack & Davis 2009). A família conta com 246 gêneros e aproximadamente 6.300 espécies (Wurdack et al 2005) distribuídas em todo o mundo, principalmente nas regiões tropicais (Govaerts et al 2000).…”
Section: Introductionunclassified
“…A família já foi incluída na ordem Linales por Cronquist (1981), porém recentes estudos moleculares e morfológicos apontaram o táxon como grupo irmão de Rhizophoraceae (Wurdack & Davis 2009;Xi et al 2012), assegurando sua posição dentro da ordem Malpighiales.…”
Section: Introductionunclassified